2014
DOI: 10.3389/fphys.2014.00392
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypertrophic cardiomyopathy: functional variance among individual cardiomyocytes as a trigger of FHC-phenotype development

Abstract: Familial hypertrophic cardiomyopathy (FHC) is the most frequent inherited cardiac disease. It has been related to numerous mutations in many sarcomeric and even some non-sarcomeric proteins. So far, however, no common mechanism has been identified by which the many different mutations in different sarcomeric and non-sarcomeric proteins trigger development of the FHC phenotype. Here we show for different MYH7 mutations variance in force pCa-relations from normal to highly abnormal as a feature common to all mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 57 publications
1
45
0
Order By: Relevance
“…This burst-like, stochastic on/off-switching of allele transcription should average out over time, but in case of heterozygosity with protein product of different stability, it can lead to variable expression of healthy and mutant proteins. This was recently shown by Kraft and colleagues [6,7]. Patients with heterozygous HCM-associated MYH7 gene mutation demonstrated a variable healthy:mutant ratio of mRNA expression in cardiomyocytes from the same heart [6].…”
Section: Introductionmentioning
confidence: 72%
“…This burst-like, stochastic on/off-switching of allele transcription should average out over time, but in case of heterozygosity with protein product of different stability, it can lead to variable expression of healthy and mutant proteins. This was recently shown by Kraft and colleagues [6,7]. Patients with heterozygous HCM-associated MYH7 gene mutation demonstrated a variable healthy:mutant ratio of mRNA expression in cardiomyocytes from the same heart [6].…”
Section: Introductionmentioning
confidence: 72%
“…; Brenner et al . ). In slow fibres from soleus muscle of human, it has been found that a single natural mutation occurring in the converter domain (708–780 region) of the slow β‐MHC isoform is responsible for a large change in motor stiffness.…”
Section: Discussionmentioning
confidence: 97%
“…It was previously determined that mutations in the converter domain can impair the stiffness of a myosin head and thus alter its force-generating properties without altering cross-bridge kinetics (41)(42)(43). Studies of the R723G mutation in human M2␤, which corresponds to R712G in MV, found an increase in the rigidity of the strongly bound myosin heads, which led to a 1.3-fold increase in force per myosin head (43).…”
Section: Converter Domain Mutations and The Myosin Power Strokementioning
confidence: 99%